(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: This study aimed to determine the progression of inflammatory markers after immediate internal fixation in open fractures of lower limb long bones, to improve postoperative infection diagnosis. Methods: A prospective case series study of 34 patients with open fractures of lower limb long bones undergoing immediate internal fixation at Cho Ray Hospital. White blood cell count, erythrocyte sedimentation rate, and C-reactive protein were measured preoperatively and for 5 days postoperatively. Results: In non-infected cases, C-reactive protein increased rapidly, peaked on day 2 after surgery, and normalized by day 5 after surgery; erythrocyte sedimentation rate increased slowly and remained elevated on day 5 after surgery; white blood cell count showed rapid increase and decrease. In two infected cases, C-reactive protein increased again after day 2 peak; erythrocyte sedimentation rate showed progressive increase; white blood cell count either increased continuously or showed a second peak. Conclusion: C-reactive protein and white blood cell count are reliable indicators for monitoring postoperative infection, while erythrocyte sedimentation rate has limited value in detecting postoperative infections.